CORRUPTION OFFENSES MANAGING DIRECTOR IN MAKING BUSINESS DECISIONS - Habonaran, Benedictus Satrio; Wirogioto, Ali Johardi; Wiryadi, Uyan (Awang Long Law Review, 2024)
Business decisions taken by the Board of Directors are solely an obligation for the Board of Directors so that SOE can grow sustainably, stably, and have high competitiveness, but an unavoidable reality is that a business entity does not only experience profits, but is also faced with phases of loss. Business decisions that have been made with full calculation and prudence are still not free from business risks that can result in the SOEs they manage experiencing losses, so that they are categorized as detrimental to state finances and lead to criminal justice processes. This study aims to (1) analyse losses in SOEs that can be qualified as state financial losses and (2) analyse what business decisions made by the President Director of SOEs are categorized as fulfilling the elements of corruption in criminal cases in the Central Jakarta District Court Decision Number 15/Pid.Sus-TKP/2019/PN.Jkt.Pst. This research uses normative juridical research methods using statute approach, conceptual approach, and case approach. The results showed that separated state assets are state assets originating from the state budget to be used as state equity participation in SOEs. State assets that become capital in the form of shares are no longer state assets. State assets in SOEs are limited to the ownership of the company's shares, so that if there is a loss in the SOE Persero, this is not a state loss, but a loss of the SOE. The business decisions made by the President Director of the SOE are categorized as fulfilling the elements of corruption due to a series of actions by Karen that do not entirely reflect the principle of prudence in making decisions, nor do they fully fulfil the elements of Article 97 paragraph (5) of the Limited Liability Company Law.